2008
DOI: 10.1038/onc.2008.251
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of future metastasis and molecular characterization of head and neck squamous-cell carcinoma based on transcriptome and genome analysis by microarrays

Abstract: Propensity for subsequent distant metastasis in head and neck squamous-cell carcinoma (HNSCC) was analysed using 186 primary tumours from patients initially treated by surgery that developed (M) or did not develop (NM) metastases as the first recurrent event. Transcriptome (Affymetrix HGU133_Plus2, QRT-PCR) and arraycomparative genomic hybridization data were collected. Non-supervised hierarchical clustering based on Affymetrix data distinguished tumours differing in pathological differentiation, and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(128 citation statements)
references
References 42 publications
12
116
0
Order By: Relevance
“…Mining of existing arrays is a much less labor-intensive process than real-time PCR for individual microRNAs, but only limited arrays can be mined, as not all microarrays have the relevant probe. Encouragingly, the Affymetrix probes to the relevant gene for hsa-miR-210 were both prognostic in the series of Rickman et al, 30 and were particularly predictive of long-term outcome (>50 months). The probes were not significant in our series, but there were some differences between the series, particularly in terms of site (the Rickman series having more hypopharynx tumors) and stage at diagnosis (our series containing more stage IV cases).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mining of existing arrays is a much less labor-intensive process than real-time PCR for individual microRNAs, but only limited arrays can be mined, as not all microarrays have the relevant probe. Encouragingly, the Affymetrix probes to the relevant gene for hsa-miR-210 were both prognostic in the series of Rickman et al, 30 and were particularly predictive of long-term outcome (>50 months). The probes were not significant in our series, but there were some differences between the series, particularly in terms of site (the Rickman series having more hypopharynx tumors) and stage at diagnosis (our series containing more stage IV cases).…”
Section: Discussionmentioning
confidence: 92%
“…Expression values for the genes containing the microRNA precursors and hypoxia-related genes were determined from Affymetrix GeneChips in the published datasets of Winter et al 7 and Rickman et al 30 Data were preprocessed and normalized as previously described. 7 A published 99-gene hypoxia up-regulated metagene was used that has been derived in HNSCC from genes clustering with known hypoxia-regulated genes.…”
Section: Microarray Datamentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Oncomine Ò Power Tools 21 was used to analyze the relationship between CD24 gene expression and oral cancer progression as well as patient outcome based on publically available datasets. 22,23 We found that oral cavity squamous cell carcinoma cancer patients with regional lymph node metastasis showed lower expression of CD24 mRNA compared to patients without metastasis (Fig. 1A).…”
Section: Low Cd24 Expression In Oral Cancer Is Associated With Poor Pmentioning
confidence: 96%
“…An extra dataset concerning breast carcinoma 46 was used for studying expression variability and treatment response. We also used two datasets for ovarian (TCGA consortium) 47 and head and neck carcinoma 48,49 each. The total number of tumors analyzed in this study amounts to 5953 (Table 1).…”
Section: Resultsmentioning
confidence: 99%